Access to Controlled Medications: Three Country Case Reports. Issue 1 (15th February 2021) - Ahmed, Ebtesam
Three country case reports are presented on patient access to medications controlled under the international substance control treaties. The countries discussed are Egypt, Kyrgyzstan and Guatemala. They are compared between themselves and with a small number of other countries. Actions to overcome the impeded access in these countries are suggested. This manuscript elaborates further on a review published in this journal in 2020.